Peningkatan Kesadaran Ibu Hamil tentang Pentingnya Nutrisi dan Olahraga melalui GEMPITA Bumil di Puskesmas Teratak - Khairani, Fuji; Suriana , Iin; Listiandini, Oktariya Heni; Juliatin Am, Riza Lutvia (Pusat Riset dan Inovasi Nasional, 2026)
Low levels of maternal knowledge and appropriate nutritional practices, combined with limited continuity of nutrition education from health workers, remain significant risk factors for maternal and child health problems, including stunting. The GEMPITA Program (Gerakan Edukasi MPASI Tepat dan Aman / Safe and Appropriate Complementary Feeding Education Movement) was implemented as a community service initiative to improve nutritional knowledge, skills, and practices among families in the working area of Teratak Public Health Center. The program employed structured methods, including socialization, education, training, demonstrations, mentoring, and non-formal monitoring and evaluation. The target participants were mothers with children aged 6–24 months, as well as health workers and community health cadres. Program effectiveness was assessed using pretest posttest measurements and direct observation of behavioral changes. The results demonstrated a significant improvement in maternal knowledge regarding appropriate complementary feeding, enhanced skills in age-appropriate food preparation, and improved hygienic and nutritious feeding practices. In addition, the capacity of health workers to deliver nutrition education was strengthened. Overall, the GEMPITA Program proved effective in improving family nutrition practices and reinforcing the role of the public health center in stunting prevention through a sustainable community empowerment approach.